Characterization of transitional memory CD4+ and CD8+ T-cell mobilization during and after an acute bout of exercise - Hunt, Rebekah M.; Elzayat, Mahmoud T.; Markofski, Melissa M.; Laughlin, Mitzi; LaVoy, Emily C. (Frontiers in Sports and Active Living, 2023)
T-cell subsets, including naïve (NA), central memory (CM), transitional memory (TM), effector memory (EM), and RA + effector memory (EMRA), differ in phenotype and function. T-cells are mobilized by exercise, with differences in the magnitude of mobilization between subsets. However, the response of TM T-cells to exercise has not yet been described. Further, T-cells expressing the late differentiation marker CD57 are known to be highly responsive to exercise, but the relative response of CD57 + and CD57- within T-cell subsets is unknown. We therefore aimed to characterize the exercise-induced mobilization of TM T-cells, as well as to compare the exercise response of CD57 + and CD57- cells within T-cell subsets. Methods Seventeen participants (7 female; aged 18–40 years) cycled 30 min at 80% of their estimated maximum heart rate. Venous blood obtained pre, post, and 1H post-exercise was analyzed by flow cytometry. CD45RA, CCR7, and CD28 expression within CD4 + and CD8+ T-cells identified NA, CM, TM, EM, and EMRA subsets. CD57 expression within EM, EMRA, and CD28+ T-cells was also quantified. The relative mobilization of each subset was compared by calculating fold change in cell concentration during (ingress, post/pre) and after exercise (egress,1H post/post). Cytomegalovirus (CMV) serostatus was determined by ELISA and was considered in models. Results TM CD8+ T-cell concentration was greater post-exercise than pre-exercise (138.59 ± 56.42 cells/µl vs. 98.51 ± 39.68 cells/µl, p < 0.05), and the proportion of CD8 + with a TM phenotype was elevated 1H post-exercise (1H: 32.44 ± 10.38% vs. Pre: 30.15 ± 8.77%, p < 0.05). The relative mobilization during and after exercise of TM T-cells did not differ from NA and CM but was less than EM and EMRA subsets. Similar results were observed within CD4+ T-cells. CD57 + subsets of CD28+ T-cells and of EM and EMRA CD8+ T-cells exhibited a greater relative mobilization than CD57- subsets (all p < 0.05). Conclusion These results indicate TM CD4 + and CD8+ T-cells are transiently mobilized into the blood with exercise, but not to as great of an extent as later differentiated EM and EMRA T-cells. Results also indicate CD57 identifies highly exercise responsive cells within CD8+ T-cell subsets.